2022
DOI: 10.3389/fcell.2022.826801
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Disrupts Organelle Distribution and Functions Affecting Meiotic Maturation in Porcine Oocytes

Abstract: Heat stress (HS) has been known to cause reproductive failure in animals, especially in summer. HS severely affects the developmental potential of oocytes and leads to low fertility rates. Previous studies have reported that HS compromises embryo development in bovine oocytes, and reduces ovarian development in mice, thereby impairing reproductive function in animals. However, the effect of high temperature (HT) on the organelles of porcine oocytes is unknown. In this study, we reported that exposure to HT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Heat stress is one of the most prevalent environmental stresses that negatively affects embryonic development. HT induces apoptosis in mouse follicles and increases mitochondrial ROS levels in bovine oocytes, while disrupting the arrangement of organelles in porcine oocytes 49–51 . To confirm the changes in ATF7 function in the context of stress, we used HT treatment during early porcine embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress is one of the most prevalent environmental stresses that negatively affects embryonic development. HT induces apoptosis in mouse follicles and increases mitochondrial ROS levels in bovine oocytes, while disrupting the arrangement of organelles in porcine oocytes 49–51 . To confirm the changes in ATF7 function in the context of stress, we used HT treatment during early porcine embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…HT induces apoptosis in mouse follicles and increases mitochondrial ROS levels in bovine oocytes, while disrupting the arrangement of organelles in porcine oocytes. 49 , 50 , 51 To confirm the changes in ATF7 function in the context of stress, we used HT treatment during early porcine embryonic development. We observed that HT induced the expression of pATF7 by activating P38, thereby reducing the levels of H3K9me2 and HP1 to affect the function of heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was performed as described previously. 24 Briefly, the embryos were washed three times with 1% PVA-PBS, fixed in 3.7% paraformaldehyde for 30 min at room temperature, and permeabilized with 1% Triton X-100 in PVA-PBS for 30 min at room temperature. The embryos were then incubated in 3% BSA in PVA-PBS for 1 h at room temperature.…”
Section: Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
“…In mice, the abnormal aggregation of the mitochondria also disables the functionality of MAMs, thus leading to a reduction in mitochondrial OXPHOS and the Krebs cycle. In combination, the imbalance in mitochondrial homeostasis and abnormal mitochondrial distribution caused by abnormal mitochondrial function ultimately leads to meiotic failure [ 127 , 128 ]. The deletion of Mfn2 in mouse oocytes leads to increased levels of ceramide; this induces apoptosis in oocytes by releasing cytochrome C from the mitochondria and activating caspases, thus triggering the arrest of follicular development [ 76 ].…”
Section: Mfns In the Development Of Germ Cells And Embryosmentioning
confidence: 99%